2013
DOI: 10.1111/jgh.12186
|View full text |Cite
|
Sign up to set email alerts
|

Antigen peptide transporter 1 is involved in the development of fructose‐induced hepatic steatosis in mice

Abstract: Taken together, the data suggest that TAP1(-/-) -deficient mice displayed reduced levels of CD8 cells that have a vital role in the initiation and propagation of liver inflammation and is a casual role in the beginning of fructose-induced liver damage as well as insulin resistance in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…We observed that the depletion of CD8+ T‐cells by antibody treatment protects the liver from inflammation, as evident from the lower abundance of both resident and infiltrating macrophages in the liver tissue section and fibrosis as evident from the Masson's trichrome staining of the liver tissue section. Further, the biochemical and histologic improvement observed in our CD8 antibody‐treated mice are in agreement with Arindkar et al We also observed infiltration of CD8+ T‐cells in the liver biopsies of patients with NASH. Although we have not observed infiltration of NKT cells in the liver biopsies of patients with NASH, given the progressive nature of NASH, we cannot be confident that the lack of identification of these cells is the result of transient infiltration of NKT cells.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that the depletion of CD8+ T‐cells by antibody treatment protects the liver from inflammation, as evident from the lower abundance of both resident and infiltrating macrophages in the liver tissue section and fibrosis as evident from the Masson's trichrome staining of the liver tissue section. Further, the biochemical and histologic improvement observed in our CD8 antibody‐treated mice are in agreement with Arindkar et al We also observed infiltration of CD8+ T‐cells in the liver biopsies of patients with NASH. Although we have not observed infiltration of NKT cells in the liver biopsies of patients with NASH, given the progressive nature of NASH, we cannot be confident that the lack of identification of these cells is the result of transient infiltration of NKT cells.…”
Section: Discussionsupporting
confidence: 92%
“…As described [29–31], insulin tolerance test and glucose intolerance test were performed at 31 weeks of age. An intraperitoneal glucose tolerance test (iGTT) and insulin tolerance test (ITT) were performed on nonanaesthetized mice after 8 hours' fasting.…”
Section: Methodsmentioning
confidence: 99%
“…CD8 T cells and NK T cells promote NASH and HCC through interactions with hepatocytes (18). CD8 T-cell-depleted mice are protected from the progression of NAFLD (19). In addition to its function as a pore-forming protein, perforin has been shown to play essential roles in immune surveillance, response, and homeostasis, and performs multiple biologic functions in different diseases (20,21).…”
Section: Discussionmentioning
confidence: 99%